1992
DOI: 10.1136/adc.67.10_spec_no.1185
|View full text |Cite
|
Sign up to set email alerts
|

Randomised controlled trial of colloid infusions in hypotensive preterm infants.

Abstract: Colloid infusions are often given to treat hypotension in preterm infants. The aim of this work was to assess whether it was the amount of protein or the volume of the colloid infused which accounted for the observed increase in blood pressure. Sixty preterm infants were randomised (20 in each group) to receive 5 ml/kg 20% albumin, 15 ml/kg fresh frozen plasma, or 15 mI/kg 4 5% albumin. All infusions were given at a rate of 5 ml/kg/hour in addition to maintenance fluids. The infants were randomised when hypote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(30 citation statements)
references
References 12 publications
3
25
1
Order By: Relevance
“…This differs from current NRP recommendations (1) that favor crystalloid infusion unless emergent O-negative blood is available. The findings are also different from those of three small randomized, controlled trials of NS versus ALB for the treatment of hypotension in acutely ill newborns in the NICU in which NS was found to be equivalent to ALB in improving blood pressure (9,34,35). Our findings may reflect acute increased oncotic pressure after ALB infusion compared with NS.…”
Section: Discussioncontrasting
confidence: 55%
“…This differs from current NRP recommendations (1) that favor crystalloid infusion unless emergent O-negative blood is available. The findings are also different from those of three small randomized, controlled trials of NS versus ALB for the treatment of hypotension in acutely ill newborns in the NICU in which NS was found to be equivalent to ALB in improving blood pressure (9,34,35). Our findings may reflect acute increased oncotic pressure after ALB infusion compared with NS.…”
Section: Discussioncontrasting
confidence: 55%
“…As it may decrease afterload [45,46], newborns with primary myocardial dysfunction and elevated peripheral vascular resistance are most likely to benefit from dobutamine treatment [28,56]. Multiple randomized studies have shown that dopamine is more effective than dobutamine in increasing blood pressure in the preterm infant [3,9,19,62]. A meta-analysis of the findings of these four studies confirmed this and found that fewer infants in the dopamine-treated group had treatment failure [60].…”
Section: Volume Expansion and Inotropesmentioning
confidence: 60%
“…Two studies [8,32] have demonstrated that it is the additional volume which is most in¯uential regarding BP improvement and those data [8,32], therefore, question the appropriateness of administering a colloid solution in such a clinical situation. In a randomized trial 5 ml/kg of 20% albumin (1 g/kg of albumin), 15 ml/kg of 4.5% albumin (0.675 g/kg albumin) and 15 ml/kg of fresh frozen plasma (2 g/kg protein) were administered to hypotensive (systolic BP <40 mmHg) preterm infants.…”
Section: Hypotensionmentioning
confidence: 94%